BALAI KESEHATAN JIWA DENGAN PENDEKATAN HEALING ENVIRONMENT DI SURAKARTA - Zhafran, Deva Bagus; Hardiyati, Hardiyati; Pramesti, Leny (Universitas Sebelas Maret Surakarta, 2017)
Abstract: Mental health is projected to be one of issues that would be a problem among people's live in the future. This issue is caused by a lack of knowledge and insight into the mental health community, as well as the negative stigma attached to people's perceptions of mental illness and the sufferers. The negative stigma hamper government and community efforts in creating mental health in the community. Stigma obstruct the recovery process of mental disorders that can happen to any human being and for the sufferers will be difficult to live in the midst of the general public. â€œbalai kesehatan jiwaâ€ that is designed aiming at providing a forum for people with mental disorders transition before returning to the life of society, as well as to create containers mental health services closer to the people so that the people who sought mental health can be achieved more efficiently.the concept of environmentâ€™s design Â is applied using a basic principle as the basis of healing environmental considerations whole aspects both component architecture and components forming other neighborhoods that are conducive and supportive userâ€™s mental health. This building is planned by the location, building appearance, structure, landscaping and utilities on the building considering the stimulants wich is Â received by the users from the building components.Â Keywords: Negative Stigma, Mental Health Centre, Containers Transition, Healing Environment